Substitute
and
. Then the integral is
![\displaystyle \int_0^\infty \frac{x^{\frac{2n-3}2} \tan^(-1)\left(x^(2n-1)\right)}{1 + x^(2n-1)} \, dx = \frac2{2n-1} \underbrace{\int_0^\infty (\tan^(-1)\left(y^2\right))/(1 + y^2) \, dy}_I](https://img.qammunity.org/2023/formulas/mathematics/college/yf6qodu1zgljl582x819dzfwrms81wubnj.png)
which is to say, the integral is now independent of n. Then
![\displaystyle \sum_(n=1)^\infty (-1)^(n+1) \int_0^\infty \frac{x^{\frac{2n-3}2} \tan^(-1)\left(x^(2n-1)\right)}{1+x^(2n-1)} \, dx = I \sum_(n=1)^\infty (2(-1)^(n+1))/(2n-1)](https://img.qammunity.org/2023/formulas/mathematics/college/9jvmpumbazbmnzidxjys7iuk919w53uc30.png)
Let's evaluate the sum. Recall that if |x| < 1, we have
![\displaystyle \frac1{1-x} = \sum_(n=0)^\infty x^n](https://img.qammunity.org/2023/formulas/mathematics/college/p1b5eswgxh6dc9rrs2d5e1cbfdwdluymwv.png)
which means
![\displaystyle \frac1{1+x^2} = \frac1{1-(-x^2)} = \sum_(n=0)^\infty \left(-x^2\right)^n = \sum_(n=0)^\infty (-1)^n x^(2n)](https://img.qammunity.org/2023/formulas/mathematics/college/huf2n13xtpehiqc6d96mp4v0i2ay22a6ji.png)
By the fundamental theorem of calculus, integrating both sides gives
![\displaystyle \tan^(-1)(x) = \sum_(n=0)^\infty (-1)^n (x^(2n+1))/(2n+1) = \sum_(n=1)^\infty (-1)^(n+1) (x^(2n-1))/(2n-1)](https://img.qammunity.org/2023/formulas/mathematics/college/mp412asl1uw5b7zvri8neufysm7wtlb7uu.png)
As x approaches 1 from below, we have
![\displaystyle \lim_(x\to1^-) \tan^(-1)(x) = \lim_(x\to1^-) \sum_(n=1)^\infty (-1)^(n+1) (x^(2n-1))/(2n-1)](https://img.qammunity.org/2023/formulas/mathematics/college/z7s39oxxidgzkns81ljh139o3alj7kt1ck.png)
![\displaystyle \frac\pi4 = \sum_(n=1)^\infty ((-1)^(n+1))/(2n-1) \left(\lim\limits_(x\to1^-) x^(2n-1)\right) = \sum_(n=1)^\infty ((-1)^(n+1))/(2n-1)](https://img.qammunity.org/2023/formulas/mathematics/college/u4crbbktp1zunqiwespg9x49u51v67giib.png)
and so
![\displaystyle \sum_(n=1)^\infty (-1)^(n+1) \int_0^\infty \frac{x^{\frac{2n-3}2} \tan^(-1)\left(x^(2n-1)\right)}{1+x^(2n-1)} \, dx = \frac\pi2 I](https://img.qammunity.org/2023/formulas/mathematics/college/ampi6l5im7mkfutly8r6hiz58zdsxqkv08.png)
Now compute the remaining integral. First split it at y = 1 :
![\displaystyle I = \int_0^1 (\tan^(-1)\left(y^2\right))/(1 + y^2) \, dy + \int_1^\infty (\tan^(-1)\left(y^2\right))/(1 + y^2) \, dy](https://img.qammunity.org/2023/formulas/mathematics/college/z34owbd2yln17w0i716qj3n0vqj0k6jijd.png)
In the second integral, notice that replacing
and
yields
![\displaystyle \int_1^\infty (\tan^(-1)\left(y^2\right))/(1 + y^2) \, dy = - \int_1^0 \frac{\tan^(-1)\left(\frac1{z^2}\right)}{1 + \frac1{z^2}} \, (dz)/(z^2) = \int_0^1 \frac{\tan^(-1)\left(\frac1{z^2}\right)}{1+z^2} \, dz](https://img.qammunity.org/2023/formulas/mathematics/college/27hvv3y504e8vyz5dxhamsl3fmimf9tsle.png)
The inverse tangent function has the property
![\tan^(-1)(x) = \frac\pi2 - \tan^(-1)\left(\frac1x\right)](https://img.qammunity.org/2023/formulas/mathematics/college/4x0vaqn0x1jw9y0kzjib2zb6wh50higohk.png)
so it follows that
![\displaystyle \int_0^1 \frac{\tan^(-1)\left(\frac1{z^2}\right)}{1+z^2} \, dz = \frac\pi2 \int_0^1 (dz)/(1+z^2) - \int_0^1 (\tan^(-1)(z^2))/(1+z^2) \, dz](https://img.qammunity.org/2023/formulas/mathematics/college/pxbzn63dpemsn36do7iitiyl7spsns6ers.png)
and hence
![\displaystyle I = \int_0^1 (\tan^(-1)\left(y^2\right))/(1 + y^2) \, dy + \frac\pi2 \int_0^1 (dz)/(1+z^2) - \int_0^1 (\tan^(-1)(z^2))/(1+z^2) \, dz](https://img.qammunity.org/2023/formulas/mathematics/college/c4rghqy2idkcqekec905b7qjpfp8kj8c0k.png)
![\displaystyle I = \frac\pi2 \int_0^1 (dz)/(1+z^2)](https://img.qammunity.org/2023/formulas/mathematics/college/mxbfl9f4jtcov0jzyj2ar6rymw2i5tnztc.png)
![I = \frac\pi2 * \frac\pi4 = \frac{\pi^2}8](https://img.qammunity.org/2023/formulas/mathematics/college/3vo926kijqjfop0ck1x1dmygubvuo8wnma.png)
Then the original expression has an exact value of
![\displaystyle \sum_(n=1)^\infty (-1)^(n+1) \int_0^\infty \frac{x^{\frac{2n-3}2} \tan^(-1)\left(x^(2n-1)\right)}{1+x^(2n-1)} \, dx = \frac\pi2 * \frac{\pi^2}8 = \boxed{(\pi^3)/(16)}](https://img.qammunity.org/2023/formulas/mathematics/college/364b93pjtw3lkaqdqd7cqz1d297ajt9zev.png)